Correlates of Nonanemic Iron Deficiency in Restless Legs Syndrome - Xiao-Ying Zhu; Ting-Ting Wu; Hong-Ming Wang; Xuan Li; Ling-Yan Ni; Tian-Jiao Chen; Meng-Yao Qiu; Jun Shen; Te Liu; William G. Ondo; Yun-Cheng Wu (Frontiers in Neurology, 2020)
Objective: Iron deficiency anemia (IDA) is a well-known cause of secondary restless legs syndrome (RLS). Iron deficiency without anemia (IDNA) is insidious, and its association with RLS is less evaluated. We investigate prevalence and features of IDNA in a consecutive cohort of patients with RLS.Methods: We included sequential primary RLS patients and RLS patients with IDA. We also recruited age- and gender-matched healthy controls. RLS mimics and other comorbidities were carefully excluded.Results: One-hundred and ninety-six RLS patients without anemia, 26 RLS patients with IDA, and 63 controls were included. 42.3% of RLS patients without anemia had iron deficiency. Women were much more susceptible for IDNA with a relative risk of 5.51 (p < 0.0001). Women with IDNA and RLS had younger age both at interview and at RLS onset compared to women with RLS without iron deficiency (NID) (P < 0.01). IDNA RLS patients showed a tendency to higher risk of severe/very severe tiredness or sleepiness during the day as compared to NID RLS patients. Furthermore, IDNA RLS patients had longer duration of RLS (P < 0.01 in men, P < 0.05 in women) and younger age at onset (only in men, P < 0.05) compared to IDA RLS patients.Conclusion: IDNA is frequent in RLS and iron deficiency may be severe despite a normal hemoglobin level. Women are at much higher risk for IDNA, and IDNA in women presents some specific clinical features. Features of IDNA RLS are different from IDA RLS. Regular screening of peripheral iron parameters even in patients with normal blood counts is recommended for timely optimal management.